Cross-disciplinary and cross-linguistic manifestation of theme in academic writing - Ebrahimi, Seyed Foad; Chan, Swee Heng; Tan, Bee Hoon (Universiti Putra Malaysia Press, 2014)
There is considerable agreement among linguists that theme acts as a cohesive device in texts. It plays a major role in message organization and in enabling it to be communicated and understood clearly. Although one issue in writing is how writers apply this cohesive device in their writing, the question of how theme manifestation is affected by the writers’ disciplinary or linguistic background has received little attention. Therefore, this paper aims to review the issue of theme in cross-disciplinary and cross-linguistic studies. The reviewed studies supported the earlier claim that theme application is packed differently across different disciplines and linguistics.